2006
DOI: 10.1086/508889
|View full text |Cite
|
Sign up to set email alerts
|

Possible Compartmentalization of Hepatitis C Viral Replication in the Genital Tract of HIV‐1–Coinfected Women

Abstract: Our data suggest that the genital and plasma quasi species represent distinct subpopulations, which possibly reflects compartmentalized viral replication. Alternatively, cell carriers harboring viral quasi species in the genital tract that are distinct from those in plasma could transfer the virus through the barrier separating the 2 body sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…It has been suggested that HCV RNA replication in PBMCs may occur in HIV/ HCV co-infected patients, but not in those with HCV alone [71]. HCV has also been isolated from cervicovaginal lavage fluid [72] in HIV infected women but not in women with HCV alone [73]. This may partially explain the increase in HCV activity and sexual transmission in HIV co-infected patients.…”
Section: Hiv and Hcv Co-infectionmentioning
confidence: 99%
“…It has been suggested that HCV RNA replication in PBMCs may occur in HIV/ HCV co-infected patients, but not in those with HCV alone [71]. HCV has also been isolated from cervicovaginal lavage fluid [72] in HIV infected women but not in women with HCV alone [73]. This may partially explain the increase in HCV activity and sexual transmission in HIV co-infected patients.…”
Section: Hiv and Hcv Co-infectionmentioning
confidence: 99%
“…This particular cell tropism is known to be influenced by the 5 0 UTR nucleotide sequence, [17][18][19] which could differ in plasma compared with other compartments or according the route of infection. 20 All of these studies represent single timepoint comparisons between compartments, and so are limited in demonstrating the evolution or stability over time.…”
Section: Moretti Et Almentioning
confidence: 99%
“…9 This increase in diversity seems to reflect an improved selective pressure, requires time to develop, 10 and is seen mostly in patients with virologic and CD4 T-cell responses to HAART. 17,19 With successful immune response, it would be reasonable to predict that enhanced control of HCV would result. As a consequence, a greater recognition of virus-infected hepatocytes and consequent alanine aminotransferase (ALT) flares are expected to occur.…”
mentioning
confidence: 99%
“…12 The remainder did not assess the presence of blood or hemoglobin in connection with detection of HCV RNA. [13][14][15][16] Thus, studies to date have not explored the relationship between HCV shedding in cervicovaginal fluids and the presence of menstrual or other blood in the female genital tract.…”
Section: Introductionmentioning
confidence: 99%